A survey of medical students’ and doctors’ knowledge of nutritional correction - Saulius Bradulskis; Kęstutis Adamonis; Julita Cicėnienė; Juozas Kutkevičius; Augustė Sutkutė; Erika Birgiolaitė; Narimantas Evaldas Samalavičius; Linas Urbanavičius; Donatas Venskutonis (Lietuvos Chirurgija, 2014)
Background / objective The nutritional state of hospitalized patients is far from ideal. A way to improve it is to develop the personnel’s theoretical and practical background on nutritional correction. Our aim was to survey the level of knowledge among physicians in Lithuanian medical institutions and students of the Lithuanian University of Health Sciences with regard to nutritional insufficiency and its correction. Methods A random voluntary questionnaire survey was undertaken. The questionnaire was completed by the university and municipal hospital physicians, primary care physicians, residents, 5th–6th year students of the Faculty of Medicine and the 3rd year students of the Faculty of Nursing of the Lithuanian University of Health Sciences. Answers to the questionnaire reflected the theoretical and practical background of the respondents. Results Overall, 134 doctors and 67 students or residents anonymously completed the questionnaire with the response rate of 100%. The median of correct answers was 8.5 (6–10) among the university hospital doctors who scored best. Primary care physicians showed the worst knowledge with the median score of 4 (1–6), p < 0.05. Doctors showed a significantly better knowledge than students did (p < 0.001). Conclusions Overall, there is a poor knowledge with regard to the incidence of malnutrition. Hospital doctors have a better knowledge of nutritional correction than both the primary car that their theoretical knowledge is worse as compared with that of doctors. A much more intense professional education is crucial to improve the nutritional state of patients in the hospitals as well as in the ambulatory practice. Key words: nutritional correction, professional knowledge, professional teaching e physicians and the students. Students’ teaching is insufficient considering